PRELIMINARY DESIGN OF ANALOG DISCRETE UNIFORM NOISE GENERATOR - Radonjic, Aleksandar (Journal on Processing and Energy in Agriculture, 2021)
The paper presents the basic idea of ​​the construction of an analog discrete uniform noise generator. The source of noise is a carbon resistor, the noise is linearly strongly amplified and limited to around zero. The probability density function (PDF) of the carbon resistor thermal noise in that region is square. By narrowing the symmetric allowable gap (interval) around zero, PDF of the noise approaches a uniform distribution. The factor of deviation from the uniform distribution is correctly and precisely defined. This quantity has been shown to be practically negligible. In addition, the paper discusses the application of the proposed ditheter noise, both in the two-bit and in the multi-bit stochastic digital measurement method (SDMM). It has been shown that noise is more suitable for application in multi-bit SDMM, because it is less sensitive to deviations from the uniform distribution. Commercially available track-and-hold circuits provide at least an order of magnitude wider bandwidth of the described generator compared to the standard solution that uses numerical random number generator and a corresponding D/A converter. However, the realization of such a generator requires hard engineering work, and therefore goes beyond the scope of this paper.
Keywords: Generator analognog diskretnog uniformnog šuma, stohastička digitalna merna metoda, digitalno-analogna konverzija.